Analysis Impact of Access to Financing on Financial Institutions , Systems Recording Finance , and Cash Management of Sustainability of MSMEs in the Regency Bojonegoro - Citra Amalia Dewi; Dani Budi Zakariya; Elvia Agustina; Furi Anggraini; Maulana Aza Mahmudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Study This aiming For analyze influence access financing , system recording finance , and cash management towards sustainability of Micro , Small and Medium Enterprises (MSMEs) stalls meatballs in Regency Bojonegoro . Research sample consists of of 30 UMKM stall players selected meatballs​ by purposive sampling. Data were analyzed using validity , reliability and t-test tests . Research result show that system recording finance own influence significant to sustainability of UMKM stalls meatballs in Bojonegoro . Increasingly Good system recording applied finance , the more tall possibility business For persist . On the contrary , access financing No show influence significant to sustainability business . Findings This indicates that UMKM in Bojonegoro need more notice repair system recording finance they . This is can done through training , mentoring , or use technology information . In addition , research this also highlights importance internal factors such as quality products , marketing strategies , and capabilities management in determine sustainability business .